On the stability of the distribution function of the composed random variables by their index random variable - Nguyen, Huu Bao (H. : ĐHQGHN, 2017)
Let us consider the composed random variable, are independent indentically distributed random variables and V is a positive value random, independent of all. In [1] and [2], we gave some the stabilities of the distribution function of 7] in the following sense: the small changes in the distribution function of Ẹk only lead to the small changes in the distribution function of TỊ. In the paper, we investigate the distribution function of TỊ vvhen we have the small changes of the distribution of V.